Combined eye-tracking and luminance measurements while driving on a rural road: Towards determining mesopic adaptation luminance. (December 2014) - Cengiz, C; Kotkanen, H; Puolakka, M; Lappi, O; Lehtonen, E; Halonen, L; Summala, H
In order to implement the recommended Commission Internationale de l'Eclairage (CIE) system for mesopic photometry to roads, it is necessary to define the relevant visual field and adaptation luminance in night-time driving conditions. We measured three drivers' eye tracking on a rural road at night and in daytime, and the simultaneous luminance for the corresponding parts of the scene on lit and unlit sections of the road at night. Fields of view with circular sizes of 1°, 5°, 10°, 15° and 20°, with the centre point at the mode of the gaze distributions of the drivers, were used as initial estimates of the visual adaptation field. In both the lit and unlit sections, the variation within subject and between subjects in the mean luminance decreased as the size of the circular field increased. However, the mean luminances of all of the circular fields in the unlit section were higher than in the lit section due to the use of high-beam headlights in the unlit section.